Breaking Carbon–Fluorine Bonds with Main Group Nucleophiles - Coates, Greg; Rekhroukh, Feriel; Crimmin, Mark R. (Synlett, 2019)
In this Account we describe a series of new reactions that we, and others, have reported that involve the transformation of C–F bonds into C–Mg, C–Al, C–Si, C–Fe and C–Zn bonds. We focus on the use of highly reactive main group nucleophiles and discuss aspects of reaction scope, selectivity and mechanism.1 Introduction1.1 The Fluorocarbon Industry and Sustainability1.2 Production of Fluorocarbons1.3 Properties of Fluorocarbons1.4 Our Work2 Results and Discussion2.1 Low-Valent Main Group Compounds2.1.1 Reactions with Fluoroarenes2.1.2 Reactions with Fluoroalkanes2.1.3 Reactions with Fluoroalkenes2.2 Main Group Nucleophiles (M1–M2)2.2.1 Reactions of M1–M2 Nucleophiles with Fluoroarenes2.2.2 Reactions of M1–M2 Nucleophiles with Fluoroalkanes2.2.3 Reactions of M1–M2 Nucleophiles with Fluoroalkenes3 Summary and Perspective
Keywords: fluorine; fluorocarbons; main group; reaction mechanisms; C–F bond activation